Performance Enhancement of Electrical Distribution Systems with Multiple Distributed Generation Sources - Sharma, Manjunatha; Koppal, Panduranga Vittal (Distributed Generation & Alternative Energy Journal, 2010)
The recent trends in electrical power distribution system operation and management are aimed at improving system conditions in order to render good service to the customer. Reforms in the distribution sector have given major scope for employment of distributed generation (DG) resources which will boost system performance. This article proposes a heuristic technique for allocation of multiple distribution generation sources in a distribution system. The allocation is determined based on overall improvement in network performance parameters like reduction in system losses, improvement in voltage stability, improvement in volt- age profile. The hybrid of Genetic Algorithm with the proposed Network Performance Enhancement Index (NPEI) along with the heuristic rules facilitates determination of feasible location for insertion of DG sources. A priority list is prepared with decreasing values of NPEI so that the designer can select most feasible locations. The developed approach is tested with different test systems to ascertain its effectiveness.